Priming mechanisms with additions of pyrogenic organic matter to soil. (1st October 2018) - DeCiucies, Silene; Whitman, Thea; Woolf, Dominic; Enders, Akio; Lehmann, Johannes
Abstract: Additions of pyrogenic organic matter (PyOM) to soil have been shown to both increase and decrease mineralization of native soil organic carbon (nSOC). This change in mineralization rate is referred to as priming, and may have important implications for carbon (C) turnover in soil. This study quantifies both positive and negative priming mechanisms using high-resolution carbon dioxide (CO2 ) measurements using a series of short-term incubation experiments with 13 C-labeled PyOM added to a temperate forest soil. Moisture, nutrient availability and pH were adjusted to minimize any differential effects on nSOC mineralization. Irrespective of pyrolysis temperature (200–750 °C), addition of 10 mg PyOM g −1 soil significantly decreased mineralization of nSOC. Dilution was measured against inorganic bulking materials with different surface areas and accounted for 19% of negative priming observed at day 7, and 13% at day 35. In comparison, substrate switching caused only 1% of negative priming assumed to be equivalent to PyOM mineralization itself. Inhibition did not explain reductions in nSOC mineralization since the microbial biomass did not significantly decrease (p > 0.05). Sorptive protection of dissolved organic carbon (DOC) was responsible for the majority of negative priming observed with PyOM additions based on adsorption isotherm experiments as well as co-location of nSOC on PyOM surfaces shown by nanoSIMS. Maximum sorption of soil DOC was 29 times higher to PyOM pyrolyzed at 450 °C than to topsoil, and tripled with an increase in pyrolysis temperature to 750 °C. This tripling in DOC sorption potential to PyOM produced at 750 °C in comparison to 450 °C was only reflected in a less than twice lower nSOC mineralization. Sorptive protection was with 80% the dominant negative priming mechanism on monthly timescales and likely beyond. These results have implications for long-term SOC storage, because sorption has more persistent effects than substrate switching or dilution.